Effect of notch root radius on tensile behaviour of 316L(N) stainless steel. (August 2014) - Ganesh Kumar, J.; Nandagopal, M.; Parameswaran, P.; Laha, K.; Mathew, M. D.
<x content-type="archive" xml:space="preserve">Abstract</x> Type 316L(N) stainless steel (SS) is used as the major structural material for high temperature components of sodium cooled fast reactors. The influence of notch root radius on the tensile behaviour of 316L(N) SS under multi-axial stress state was investigated. Double U-notches with five different kinds of notch geometry were incorporated symmetrically into the tensile testing specimens by changing the notch root radius while keeping the gross diameter, net diameter and notch depth as the same for all the notches. The notch root radius was varied as 0·25, 0·5, 1·25, 2·5 and 5 mm. Tensile tests were carried out on the notched specimens at room temperature (298 K) and at 923 K at a constant strain rate of 3×10−3 s−1. The tensile strength and yield strength of notched specimen of 316L(N) SS increased with decrease in notch radius at both the temperatures and the notch severity was less pronounced at high temperature. The fractured notch surface was analysed using scanning electron microscope and unfractured notch was sliced along the axis and observed under optical microscope. Finite element analysis was performed on the models of notched specimens with various notch root radii. These results showed that Von Mises equivalent stress which was derived from triaxial stresses decreased with decrease in notch radius. The shift of location of peak values of maximum principal stress and hydrostatic stress towards the axis of the specimen, leading to formation of cracks, occurred at a lower nominal stress when the notch radius was increased.